Encyclopedia of religion, communication, and media - Stout, Daniel A. (Routledge encyclopedias of religion and society., 2006)
Explores the various forms of religious communication worldwide, with a special emphasis on oral and written forms of communication. This work analyzes how and why the world's religions have used different means of communications. It is intended for scholars, students, as well as the general reader interested in religion, media, or communications.